Key endoscopic ultrasound features of pancreatic ductal adenocarcinoma smaller than 20 mm. (March 2014) - Aso, Akira; Ihara, Eikichi; Osoegawa, Takashi; Nakamura, Kazuhiko; Itaba, Soichi; Igarashi, Hisato; Ito, Tetsuhide; Aishima, Shinichi; Oda, Yoshinao; Tanaka, Masao; Takayanagi, Ryoichi
Abstract Background and study aims. Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis compared with other solid pancreatic tumors. Diagnosis of PDAC in the earliest possible stage is important to improve the prognosis. Although endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) has been the gold-standard modality for diagnosing pancreatic lesions, its diagnostic yield is not satisfactory for pancreatic tumors smaller than 20 mm. The purpose of this study was to determine the EUS findings that are useful for differentiating PDAC from other solid pancreatic tumors when the lesions are smaller than 20 mm. Patients and methods. We performed a retrospective review of 126 patients with pancreatic tumors smaller than 20 mm who had undergone EUS. According to the final pathological diagnoses, they were categorized into either the PDAC or non-PDAC group. We, then, compared the EUS findings between the two groups. Results. Among the 126 patients, we diagnosed PDAC in 75 patients and non-PDAC in the remaining patients, including neuroendocrine tumor in 43 patients, intraductal papillary mucinous carcinoma in 3 patients, solid pseudopapillary neoplasm in 2 patients, and inflammatory pseudotumor in 3 patients. Of all EUS findings, three factors were significantly indicative of PDAC: an irregular tumor edge, main pancreatic duct dilation, and tumor location in the pancreatic head. The predicted probability for PDAC was 80%, 92.6%, and 74.1%, respectively. Conclusions. EUS could be a useful modality for differentiating PDAC from other solid pancreatic tumors, when the diagnostic yield of EUS-FNA is unsatisfactory, even for lesions smaller than 20 mm.